(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
The history of irrigation farming in the Surkhan-Sherabad oasis goes back a long way. Extensive scientific research conducted in the oasis, as well as material sources found in the course of archaeological excavations, provide the necessary information about this. "Southern Surkhan Reservoir" has an incomparable role in the flourishing of the Surkhan-Sherabad oasis. This article talks about the history of establishment and water saturation of "Southern Surkhan Reservoir", which has been operating for half a century (Topolang Daryo, Karatog Daryo, Sangardak Daryo, Khojaipok Daryo).